2021
DOI: 10.33448/rsd-v10i12.20140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cysts and odontogenic tumors over a period of 8 years in a reference medical hospital in Brazil

Abstract: Objective: This study aimed to evaluate the relative prevalence, demographic distribution and clinical-pathological characteristics of the maxillary odontogenics cysts and tumors of the jaws in a pathology laboratory located in a university hospital in Northeastern Brazil. Methods: An observational and retrospective study was carried out, in which information was collected on histopathological diagnosis, age, gender and location of the lesion of patients who had been diagnosed with odontogenic cysts or odontog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…According to the age of patients, it differs from 6 years old to 80 years old, with a mean of 32.4 ± 16.4. The present study revealed that the odontogenic cysts mainly occurred in the 2 nd and the 3 rd decades of life, which is in line with studies from Mexican [9], Brazilian [12], Indian [10], and Iranian populations [14]. Furthermore, of the 368 odontogenic cyst patients, 222 (60.33%) were males and 146 (39.67%) were females.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…According to the age of patients, it differs from 6 years old to 80 years old, with a mean of 32.4 ± 16.4. The present study revealed that the odontogenic cysts mainly occurred in the 2 nd and the 3 rd decades of life, which is in line with studies from Mexican [9], Brazilian [12], Indian [10], and Iranian populations [14]. Furthermore, of the 368 odontogenic cyst patients, 222 (60.33%) were males and 146 (39.67%) were females.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, of the 368 odontogenic cyst patients, 222 (60.33%) were males and 146 (39.67%) were females. With a male-to-female ratio of about 1.52:1 (Tables 2 and 3), which was consistent with research performed in other countries, including Portugal, Brazil, Mexico, Italy, India, Kenya, Greece, Turkey, Italy, and Iran (ranging between 50.9 % and 64.4 %) [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. In contrast, female predominance was significant in the Brazilian population [26] and among Indonesians [24].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…It is slow-growing and asymptomatic, and its principal location is in the jaw. AB constitutes 11% of odontogenic tumors 5 , and it is more common in men than in women 6 . Clinically, it presents as a swelling with the expansion of bone cortices, sometimes accompanied by dental mobility and displacement 7,8 .…”
Section: Ameloblastomamentioning
confidence: 99%